Effects of the dementia care toolbox on personnel’s self-reported confidence in patient care: a CRT in general practices - Sabine Christine Jäger (BMC, 2021)
Abstract Background In rapidly aging populations, general practitioners (GPs) are challenged in dementia care of patients with and without migration background. Uncertainties in treating dementia in migrant patients due to language barriers or information deficits are reported. To address these deficits, we developed the Dementia Care Toolbox which was judged helpful by GP practice personnel. This two-armed cluster-randomised trial (CRT) investigated the effects of this toolbox on German GPs’ and practice assistants’ (PrAs) attitudes and confidence in dementia care, especially in patients with migration background. Methods A total of 32 GP practices were recruited and randomised into intervention (toolbox use for 3 months) and waiting-list control (toolbox after follow-up). After 3 months all participating GPs and PrAs received a standardised questionnaire addressing their levels of self-reported confidence in dementia care for patients with and without migration background. A generalized estimating equation model that took practice cluster effects into account was applied to assess GPs and PrAs self-reported confidence in dementia care in patients with and without migration background. Results Overall, the intervention had no significant effect on self-reported confidence in dementia care. However, the use of the dementia care toolbox showed a tendency for a learning effect on knowledge about local support structures for migrant patients with dementia (odds ratio 1.43; 95% CI 0.68-3.03, p = 0.35) and for less communication difficulties with dementia patients in general (odds ratio 0.72; 95% CI 0.33-1.56; p = 0.40). Moreover, intervention practices showed a tendency towards more awareness of own limitations: less self-confidence regarding answering questions (odds ratio 0.82; 95% CI 0.36-1.86, p = 0.64) and providing information for patients with migration background (odds ratio 0.60; 95% CI 0.25-1.45, p = 0.26). Conclusion The Toolbox Dementia Care increased awareness on the respective topic. Given a small sample size, further studies on its effectiveness in primary care are needed. Trial registration German Clinical Trials Register, DRKS00014632. Registered 02/08/2018.